Unrecognised ringside concussive injury in amateur boxers - Moriarity, J. M.; Pietrzak, R. H.; Kutcher, J. S.; Clausen, M. H.; McAward, K.; Darby, D. G. (British Journal of Sports Medicine, 2012)
Objectives Concussion is common in contact sports such as boxing. Diagnosis of concussion depends on symptom report or recognition of clinical features, and true incidence may be underestimated. Persistent morbidity is a possible risk of repeated or unrecognised concussion. This study aimed to evaluate pre and postbout cognitive performance in motivated amateur boxers in order to detect objective evidence of unrecognised cognitive impairment suggestive of concussive injury.Methods The study employed a prospective and observational design. Participants were amateur boxers who won at least one bout in a single elimination competition. Optimal preparticipation performance using a computerised cognitive assessment tool (CCAT, Axon Sports) and no significant deterioration in cognitive performance within 24 h postbout were required to compete. All boxers were screened for clinical evidence of concussion by a ringside physician.Results Of approximately 200 competing boxers, 96 were eligible having won at least one of the total 160 bouts. Mean age was 21.3 (SD 1.9) years (range 18.5-29.7). Of these, 17 (10.6%) failed their first postbout CCAT, with 12 (71%) passing a repeat test. Of the five remaining boxers, there were two boxers (1.3% of bouts) not suspected of a concussion after their bouts, who showed evolving slowing in cognitive performance typical of a concussion.Conclusions Cognitive impairment, as detected by subtle deterioration in reaction time measures, can occur in amateur boxers postbout that is not recognised at ringside. Although the vast majority of bouts were conducted safely, unrecognised injury may occur and be detectable using objective computerised cognitive assessment.